2022
DOI: 10.3389/fnagi.2022.777700
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Social Isolation-Induced Autophagy Inhibition and Cell Senescence Aggravate Cognitive Impairment in D(+)Galactose-Treated Male Mice

Abstract: Aging is associated with physiological and pathological changes and presents health complications, such as dementia. Isolation has also been associated with the experience of growing old. Both have been linked individually to the incidence of cognitive decline. In this present study, the effects of these two phenomena have been looked at in animal models where aging was induced with D(+)Galactose in mice who underwent long-term post-weaned social isolation (L-PWSI). Assessing cognitive function using Y-maze, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…In this study, we employed the open field test, Y-maze test, and novel object recognition to evaluate the impact of L. plantarum CCFM8661 on the cognitive function of d -galactose-induced aging in mice. The experimental results revealed that aging mice exhibited cognitive impairment along with symptoms of anxiety and depression, which aligns with the results of previous studies 19,33 and also confirms the successful establishment of the aging model. Excessive d -galactose triggers oxidative stress, which is a key factor in aging.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we employed the open field test, Y-maze test, and novel object recognition to evaluate the impact of L. plantarum CCFM8661 on the cognitive function of d -galactose-induced aging in mice. The experimental results revealed that aging mice exhibited cognitive impairment along with symptoms of anxiety and depression, which aligns with the results of previous studies 19,33 and also confirms the successful establishment of the aging model. Excessive d -galactose triggers oxidative stress, which is a key factor in aging.…”
Section: Discussionsupporting
confidence: 90%
“…Open Field Test (OFT). The OFT was performed to assess the basic locomotor activity and anxiety-like behavior [16,17]. Each mouse was allowed to move and explore freely in an open field box (black, L40 × W40 × H40 cm) for 10 min (Figure 2A).…”
Section: Behavioral Testsmentioning
confidence: 99%
“…A camera placed above the box was used to record its movement. Data on the total distance moved, speed, and time spent in the center zone of the field was recorded and analyzed [16,17]. consists of three black plastic arms (L30 × W7.5 × H15 cm, Figure 3E).…”
Section: Behavioral Testsmentioning
confidence: 99%